Analisis Efektifitas Implementasi Gapeka dan Standar Pelayanan Minimum di PT KAI Divisi Regional II Sumatera Barat - Handoko; Wahyu Pratama, Andri; Seta Anggara, Yogi; Wan Ibnu, Happy; Sutomo Putra, Lopan (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2020)
The Changing of train departures, train arrivals, and travel times affect the application of GAPEKA at PT. KAI Regional II division of West Sumatera. The importance of applying the minimum standards service will affect the level of satisfaction of train users. This study aims to: 1) analyze the constraints that occur in the West Sumatra region, especially Regional Division II in the operation of railroad traffic, 2) what are the elements that affect the Railroad Travel Chart (GAPEKA) in the region West Sumatra, and 3) what is the minimum service standard for train users in the region especially West Sumatra Division II. This research used descriptive qualitative. Based on the results of analysis in the field that 98% of Regional II West Sumatra stations have implemented minimum service standards that refer to PM No. 63 of 2019 concerning transportation of people by train which includes safety, security, reliability, comfort, convenience and equality. This can have a positive effect on the effective implementation of services, such the structure and mechanism of proper work. By implementing GAPEKA and increasing minimum service standards based on PM No. 63 of 2019 which aims to provide maximum service to train users in West Sumatra and to improve the quality of services in the field of railways